Enuresis profile in 6-7 year-old children at five elementary schools in Sario district, Manado - Adrian Umboh; Astrid A. Malonda; T. A. Sudjono (Indonesian Pediatric Society, 2007)
Background Enuresis is inappropriate urination by a child whohas reached an age which bladder control is expected. The etiologyis unknown, but some factors influence it.Objective To identify enuresis profiles in 6-7 year-old children.Methods It was a descriptive prospective study at five elementaryschools in Sario district Manado from May to September 2005.Data were obtained by questionnaires.Results Out of 63 children with enuresis, 67% aged 6 years, 57%were male, 37% had enuresis more than 4 times a month, 64%had enuresis more than 8 times a day. No one had complaint ofurinary tract infection. Most cases (70%) had enuresis since birth,51% of cases got toilet training at the age of 3-4 years old. Noneof enuretic children had divorced parents. Nocturnal enuresisoccurred in 81% of cases, 54% of cases had 4 family members,30% of cases had family history of enuresis.Conclusions Enuresis in 6-7 year old children is most commonlyseen in boys. Enuresis mostly happens for more than 4 times in amonth with urination more than 8 times a day. There is nocomplaint of urinary tract infection. Most of the cases haveenuresis during nighttime. Toilet training starts by the age 3-4years old. Most cases had enuresis since birth. They came from afamily with 4 family members, and in most situation no familyhistory of enuresis is found.